The Influence Of Prices And Online Customer Reviews On The Decision To Purchase Safarry Sandals At Lazada (Survey on Safarry Sandal Consumers on the Lazada Marketplace) - Maulana, Algi; Lestari, Suci Putri; Wibawa, Gian Riksa (Utami Publisher, 2024)
This research aims to determine the influence of price and online customer reviews on purchasing decisions for Safarry sandals at Lazada. The method used is quantitative with a research sample of 100 respondents. The data used are primary and secondary data. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25. Based on the results of this research, it shows that Price and Online Customer Reviews simultaneously have a positive and significant effect on Purchasing Decisions. Price partially has a significant effect on purchasing decisions. Online Customer Reviews partially have a significant effect on Purchasing Decisions.